Simultaneous small‐angle neutron scattering and Fourier transform infrared spectroscopic measurements on cocrystals of syndiotactic polystyrene with polyethylene glycol dimethyl ethers. Issue 5 (4th August 2016) - Kaneko, Fumitoshi; Seto, Naoki; Sato, Shuma; Radulescu, Aurel; Schiavone, Maria Maddalena; Allgaier, Jürgen; Ute, Koichi
Abstract : A new simultaneous measurement method combining small‐angle neutron scattering and Fourier‐transform infrared spectroscopy was applied to a study on a syndiotactic polystyrene cocrystal with polyethylene glycol dimethyl ether with a molecular weight of 500. It is suggested that the guest molecules in the crystalline region have an elongated structure along the thickness direction of the crystalline lamellae. Abstract : Syndiotactic polystyrene (sPS) is a crystalline polymer which has a unique property; it is able to form cocrystals with a wide range of chemical compounds, in which the guest molecules are confined in the vacancies of the host sPS crystalline region. Recently, it has been found that even polyethylene glycol oligomers with a molecular weight of more than several hundreds can be introduced into the sPS crystalline region. It is quite important to know how such a long‐chain molecule is stored in the host sPS lattice. To tackle this issue, a new simultaneous measurement method combing small‐angle neutron scattering and Fourier transform infrared spectroscopy (SANS/FTIR), which has been recently developed by the authors, was applied to an sPS cocrystal with polyethylene glycol dimethyl ether with a molecular weight of 500 (PEGDME500). The temperature‐dependent changes of the SANS profile and FTIR spectrum were followed from room temperature up to 413 K for a one‐dimensionally oriented SANS/PEGDME500 cocrystal sample. The intensity of the reflections due to the stacking of crystalline lamellae showed a significant temperature dependence. The two‐dimensional pattern in the high Q region of SANS also changed depending on temperature. The combined information obtained by SANS and FTIR suggested that PEGDME500 molecules are distributed in both the crystalline and amorphous regions in the low‐temperature region close to room temperature, but they are predominantly included in the amorphous region in the high‐temperature region. It was also suggested by the two‐dimensional SANS profile that PEGDME500 molecules in the crystalline region have an elongated structure along the thickness direction of the crystalline lamellae.